Effect of Religiosity, Knowledge, Morale, Education, and Ethics on Tax Compliance - Sonya Azharani Nugrahani; Sofie Yunida Putri (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This study aims to analyze the influence of religiosity, tax knowledge, tax morale, education level, and ethical perceptions of tax evasion on tax compliance among individual taxpayers registered at the Jombang Primary Tax Office (KPP Pratama Jombang). A quantitative approach was employed, with primary data collected through questionnaires from 100 respondents. Data analysis was conducted using Partial Least Square (PLS)-based Structural Equation Modeling (SEM) via SmartPLS 4.0. The results revealed that tax knowledge and tax morale significantly positively affect tax compliance, while ethical perceptions of tax evasion negatively impact compliance. Conversely, religiosity and education level showed no significant effects. These findings suggest that enhancing taxpayers’ understanding of taxation and moral motivation can improve compliance, whereas viewing tax evasion as unethical reduces non-compliant behavior. The study highlights the importance of tax education and ethical awareness campaigns by tax authorities to foster voluntary compliance. The research contributes to the literature by validating the Theory of Planned Behavior (TPB) in the context of Indonesian taxpayer behavior.